Penerapan Manajemen Risiko Menggunakan COSO: Enterprise Risk Management Framework Integrated Pada PT ALPHANET: Risiko; Manajemen Risiko; COSO Enterprise Risk Management; Kebijakan; PT Alphanet (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2022)
In order to improve the efficiency of operational activities and the quality of bank services to their customers, banks are required to develop bank business strategies by utilizing more advances in information technology to increase bank competitiveness. The application of information technology has brought changes in operational activities and bank data management so that it can be carried out more efficiently and effectively and provide information more accurately and quickly. The development of technology-based banking products includes Autometicly Teller Mecine (ATM), Electronic Data Capture (EDC), Mobile Banking, E-Money and Internet Banking. From some of these technological developments, not a few banks use the services of third parties in providing systems and services, one of which is PT Alphanet. PT Alphanet is one of the three ATM network providers in Indonesia. PT Alphanet strives to provide support for banks, financial institutions and other partners or partners by providing innovative solutions to meet their needs. The analysis process of this study uses the COSO: ERM (Enterprise Risk Management) Framework to assist PT Alphanet in implementing risk management units and can also manage risks.  The results of the analysis show that the activities in the IT units that have been identified mostly get a Low risk category, which means that risks can be accepted by management and risk management policies have also been prepared that can be applied at PT Alphanet.